Tinjauan Kriminologis Tindak Pidana Penyalahgunaan Narkotika - Nurul Widhanita Y. Badilla; Tri Novita Sari Manihuruk (Musamus University, 2023)
Narcotics abuse is an act that is contrary to laws and regulations. Currently narcotics abuse covers all levels of society whether poor, rich, old, young, and even children. Seeing the facts of the case, what are the factors that cause the crime of narcotics abuse and how are the efforts to deal with the crime of narcotics abuse. The research method used is empirical juridical. The research results show that Factors causing the crime of narcotics theft in Merauke district are economic factors, family factors, environmental factors, educational factors, and sociological factors as well as several other factors, namely, selfish feelings, the will to be free, mental turmoil, and a sense of awareness. Efforts to deal with narcotics crimes by the Merauke resort police are preventive efforts in the form of counseling and outreach through universities, schools, mass media. And repressive efforts in the form of law enforcement.